2017
DOI: 10.21608/edj.2017.76277
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Smear Layer Removal, Calcium Ions Loss and Dentin Microhardness After Different Final Irrigation Solutions

Abstract: Nonsurgical root canal treatment is a prospective procedure for saving teeth that otherwise would be extracted. Adequate cleaning and shaping of the root canal system is the golden key for establishing best possible results of the treatment 1. Endodontic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Regarding the smear layer removal assay in the current study, It was found that NaOCl/EDTA significantly removed the smear layer exposing the highest percentage of open dentinal tubules, this result coincide with recently published studies (38,39) . All tested vinegars in the current study significantly removed the smear layer compared to the saline group.…”
Section: Natural Vinegars As Endodontic Irrigantssupporting
confidence: 92%
“…Regarding the smear layer removal assay in the current study, It was found that NaOCl/EDTA significantly removed the smear layer exposing the highest percentage of open dentinal tubules, this result coincide with recently published studies (38,39) . All tested vinegars in the current study significantly removed the smear layer compared to the saline group.…”
Section: Natural Vinegars As Endodontic Irrigantssupporting
confidence: 92%
“…Singh R et al 31 has tested the antimicrobial potential and found promising results against various bacteria especially against S. typhimurium and E. aerogens. Fayyad D et al 32 compared the effect of irrigants on dentin microhardness by release of Calcium ion (Ca) from root dentin found EDTA, QMix, and Chitosan recorded the highest Ca ion loss that ultimately leads to lower the microhardness compared to NaOCl (used as control in our study). Our study revealed that the experimental irrigant (ethanolic extract of Sapindus mukorossi) showed no significant decrease in dentin micro hardness in comparison to 17% EDTA which has reduced the dentin micro hardness due to the loss of mineral content.…”
Section: Discussionmentioning
confidence: 54%
“…(Table 3) For instance, 15 min of contact with 0.2% chitosan resulted in a reduction in microhardness to 44.65 ± 3.19 VHN from the initial 57.87 ± 1.60 VHN [12]. Also, a comparison between 17% EDTA and 0.2% chitosan showed that EDTA had a significantly larger effect, decreasing microhardness to 59.68 ± 0.30 VHN as opposed to 65.00 ± 0.49 VHN for chitosan [45].…”
Section: Other Irrigantsmentioning
confidence: 97%
“…The quality assessment of the studies included in this systematic review was performed using the QUIN tool, a checklist of items for reporting in vitro studies specifically for dental related studies. Twelve studies [12,17,22,33,36,[40][41][42][43][44][45]51] were categorized as having a low risk, with the rest positioned within the medium risk category [1,8,11,15,16,[18][19][20][21][23][24][25][26][27][28][29]31,33,35,38,43,46,[48][49][50]52,53] as detailed in Figure 3.…”
Section: Study Quality and Risk Of Biasmentioning
confidence: 99%